Sex Steroids Influence Brain-Derived Neurotropic Factor Secretion from Human Airway Smooth Muscle Cells - Wang, Shengyu (J Cell Physiol, 2015)
Brain derived neurotropic factor (BDNF) is emerging as an important player in airway inflammation, remodeling, and hyperreactivity. Separately, there is increasing evidence that sex hormones contribute to pathophysiology in the lung. BDNF and sex steroid signaling are thought to be intricately linked in the brain. There is currently little information on BDNF and sex steroid interactions in the airway, but is relevant to understanding growth factor signaling in the context of asthma in men vs. women. In this study, we assessed the effect of sex steroids on BDNF expression and secretion in human airway smooth muscle (ASM). Human ASM was treated with estrogen (E(2)) or testosterone (T, 10nM each) and intracellular BDNF and secreted BDNF measured. E(2) and T significantly reduced secretion of BDNF; effects prevented by estrogen and androgen receptor inhibitor, ICI 182,780 (1uM) and flutamide (10uM), respectively. Interestingly, no significant changes were observed in intracellular BDNF mRNA or protein expression. High affinity BDNF receptor, TrkB, was not altered by E(2) or T. E(2) (but not T) significantly increased intracellular cyclic AMP levels. Notably, Epac1 and Epac2 expression were significantly reduced by E(2) and T. Furthermore, SNARE complex protein SNAP25 was decreased. Overall, these novel data suggest that physiologically relevant concentrations of E(2) or T inhibit BDNF secretion in human ASM, suggesting a potential interaction of sex steroids with BDNF in the airway that is different from brain. The relevance of sex steroid-BDNF interactions may lie in their overall contribution to airway diseases such as asthma.